Medios de Comunicación de Iberoamérica en la WebCaso de Estudio Perú - Encalada Jaramillo, Glenda Paola (2018)
Abstract:The purpose of this investigation is to analyze Iberoamerica s web media. It focusses in Perú, considering principal media like: El Comercio, América Tv, RPP Noticias, La República, Perú21, Latina Tv, Diario Correo y Perú.com. This investigation analyzes different topics of the structure of media s web portal and digital journalism as accessibility, hypertextual, interactivity, multimedia, updating and storing. Another aspects investigation includes are new profiles, professional profiles, user profiles that take place thanks to technological innovation of the web. Finally, the investigation allows to see the evolution of media in the Internet, and how the traditional media have been adapted to those changes.